SEJARAH MASYARAKAT ARAB SEBELUM DATANGNYA ISLAM: (Studi Perbandingan Pemikiran Syekh Shafiurrahman Mubarakfuri dan Philip K. Hitti) - saryadi; Kerwanto (EL-ADABI : Jurnal Studi Islam, 2023)
The history of the Qur'an in general and across schools of thought in particular will not be perfectly studied and explored if it is not accompanied by studying the history of the Arabs before the arrival of Islam because Islam first appeared in Arabia and its holy book was in Arabic. Before the advent of Islam, the Arab nation already had its own civilization, starting from the system of government to their respective beliefs. The purpose of this paper is to reveal information about the condition of Arab society before Islam from two different perspectives, namely Eastern and Western thought. In this paper, the discussion is only about the phenomenon of society in Arabia (Hijaz and its surroundings), during the period of growth and development of the Prophet Muhammad before being appointed as a prophet and beliefs and religion in the Hijaz before Islam.